(untitled) (Nepal Medical College Journal, 2024)
Ultrasonography (USG) is modality of choice for normal, diffuse or nodular thyroid diseases. Two dimensional shear wave elastography (2D-SWE) is the latest innovation in USG techniques that allows real-time quantitative assessment of tissue stiffness using acoustic radiation force impulse (ARFI) induced by ultrafast focused US beam sequence (up to 20,000Hz) to record the propagation of the shear waves in real time and displays a map that represents the local elasticity values of tissues in real-time and in a quantitative manner without any compression of the organ. At times, there are difficulties in differentiating normal thyroid gland from diffuse thyroid disease based solely on gray scale USG for which 2D-SWE can be an adjunct. This study aims to establish 2D-SWE parameters for normal thyroid gland in Nepalese population. A cross sectional descriptive study was carried out with 2D SWE on all euthyroid patients with normal thyroid gland on B-mode USG at Department of Radiology, Nepal Medical College Teaching Hospital between December 2021 and November 2022. Tissue stiffness of normal thyroid gland was recorded and tabulated in terms of SMV units (m/s) according age and gender. Out of 100 subjects ( 52 females and 48 males) the youngest was 16 year female and oldest was 68 year female with mean age of 37.07 year (S.D = 11.58). Minimum mean velocity of 1.78 m/s was seen in 36 year old male and maximum of 3.40 m/s in 26 year old female. Mean of mean velocity was 2.36 m/s with (S.D= 0.34). Linear positive correlation was seen between shear wave velocities and age with no statistically significant difference between genders. This study had the most number of normal subjects (100) with almost equal gender distribution (52 females and 48 males) compared to previous studies in known literature. This study also analyzed correlation of shear wave velocity with age unlike other studies. Statistically significant correlation was seen between age and velocities in males only and also in mean velocities between age group 21-40 and 41-60 years (p-value= 0.037).